Correlation and path analysis of agronomic and morphological traits in maize - Silva, Tallyta; Moro, Gustavo; Moro, Fabíola; Santos, Durvalina Maria; Buzinaro, Rodolfo (Revista Ciência Agronômica, 2016)
The efficiency of selection can be broadened for certain traits using estimative of genetic parameters, which are fundamental for plant breeding. The estimative of genetic parameters allows identifying the nature of the action of genes involved in the control of quantitative traits and evaluates the efficiency of different breeding strategies to obtain genetic gains. Therefore, this study aimed to verify the variability and correlation between morphological and agronomic traits in synthetic maize populations, in order to practice indirect selection. Thirteen populations were evaluated in field experiments at Jaboticabal-SP and Campo Alegre de Goiás-GO, using randomized block design, for lodging (LOD), culm breakage (CB), plant height (PH), ear height (EH) and grain yield (GY). The 13 populations were also sown in 1 kg-plastic bags under black shade cloth, using a randomized complete block design with nine replications, for evaluation of the morphological traits: main root length (MRL), root fresh matter (RFM), root dry matter (RDM), average root diameter (ARD), root surface area (RSA), root tissue density (RTD) and shoots dry matter (SDM). The trait GY exhibited genetic variability enough to be effective if used for selection. The selection on the morphological traits is indicated on RDM, due to the ease in obtaining data and its accuracy, high correlation with all morphological traits and association with GY. The simultaneous selection based on RFM and RDM, for gains in GY, can be performed. The highest direct effect on GY was identified in LOD and CB, being indicated for indirect selection.